2019
DOI: 10.1186/s12884-019-2669-9
|View full text |Cite
|
Sign up to set email alerts
|

Perinephric urinoma following spontaneous renal rupture in the third trimester of pregnancy: a case report and brief review of the literature

Abstract: Background: Spontaneous formation of urinoma is a rare condition, especially for pregnant women. We report a patient in the third trimester of pregnancy with a spontaneous renal rupture who then develops a urinoma from urine leaking into the perinephric space. Case presentation: A 23-year-old primagravida was diagnosed with a spontaneous renal rupture and acute left loin pain accompanied by hematuria when she was 35 weeks pregnant. A sub-capsular perinephric cyst then developed to a size of 319 × 175 × 253 mm,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…5). Only one patient requested, and was granted, pre-term delivery at 35 weeks secondary to pain from SRFR [19].…”
Section: Outcomes and Complicationsmentioning
confidence: 99%
“…5). Only one patient requested, and was granted, pre-term delivery at 35 weeks secondary to pain from SRFR [19].…”
Section: Outcomes and Complicationsmentioning
confidence: 99%
“…10 Although right-sided rupture is more common, there have been case reports of women with spontaneous renal system rupture during pregnancy on the left side without underlying renal conditions as well. 2,12,14,15,21,25,31,35,37,39,40,43,44,51,52 Kim et al 50 reported a case of spontaneous, bilateral renal pelvis rupture after a cesarean delivery, and we add the second case of bilateral spontaneous renal rupture to the literature.…”
Section: Pathophysiologymentioning
confidence: 97%
“…The treatment methods for renal rupture are varied. [1][2][3] The spontaneous renal rupture has been reported in many literature before, but it caused by hemophilia has hardly been reported. The report describes a rare case of left renal rupture caused by hemophilia, furthermore, the patient also had some atrophy of the right kidney.…”
Section: Introductionmentioning
confidence: 99%